2018
DOI: 10.1007/s12035-018-1193-7
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Control of the Notch and Eph Signaling Pathways by the Prion Protein: Implications for Prion Diseases

Abstract: Among the ever-growing number of self-replicating proteins involved in neurodegenerative diseases, the prion protein PrP remains the most infamous for its central role in transmissible spongiform encephalopathies (TSEs). In these diseases, pathogenic prions propagate through a seeding mechanism, where normal PrP molecules are converted into abnormally folded scrapie isoforms termed PrP. Since its discovery over 30 years ago, much advance has contributed to define the host-encoded cellular prion protein PrP as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Beyond ARSB and its association with MPS, we also noted 24 positional candidate genes related to 26 additional EMMAX GxE signals ( P -value ≤ 5E-05; Supplementary Table 2 , Fig. 1 ); the majority of which have previously been associated with Parkinson’s disease ( SMYD4 , WARS2 , IFNGR1 , PLPP4 , ASCL1 , FAM120A ), Alzheimer’s disease ( TBX15 , IFNGR , PTP4A1 , AIM2 , SLC10A2 , COL25A1 , ASCL1 , EPHB1 , UMAD1 , VNN3 , COL27A1 , RNF144B , SDK2 ), and various prion diseases ( IFNGR , SEC23IP , EPHA3 , EFNB2 , ELOVL4 , DOCK5 , COL27A1 ) including scrapie, bovine spongiform encephalopathy, and Creutzfeldt–Jakob disease ( Ide et al 2005 ; Julius 2008 ; Hashioka et al 2009 ; Tong et al 2010 ; Tian et al 2013 ; Woodling et al 2014 ; Majer 2015 ; Freeman and Ting 2016 ; Vélez et al 2016 ; Watson et al 2016 ; Mez et al 2017 ; Su et al 2018 ; Choubey 2019 ; Dabin 2019 ; Hirsch et al 2019 ; Liu et al 2019 ; Majer et al 2019 ; Meyer et al 2019 ; Thatra 2019 ; Bellenguez et al 2020 ; Dabin et al 2020 ; Donaldson et al 2020 ; Martinelli et al 2020 ; Wang et al 2020 ; Vastrad and Vastrad 2021 ). Notably, the EMMAX GxE mixed model solutions were also robust to the inclusion of additional fixed effect covariates (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Beyond ARSB and its association with MPS, we also noted 24 positional candidate genes related to 26 additional EMMAX GxE signals ( P -value ≤ 5E-05; Supplementary Table 2 , Fig. 1 ); the majority of which have previously been associated with Parkinson’s disease ( SMYD4 , WARS2 , IFNGR1 , PLPP4 , ASCL1 , FAM120A ), Alzheimer’s disease ( TBX15 , IFNGR , PTP4A1 , AIM2 , SLC10A2 , COL25A1 , ASCL1 , EPHB1 , UMAD1 , VNN3 , COL27A1 , RNF144B , SDK2 ), and various prion diseases ( IFNGR , SEC23IP , EPHA3 , EFNB2 , ELOVL4 , DOCK5 , COL27A1 ) including scrapie, bovine spongiform encephalopathy, and Creutzfeldt–Jakob disease ( Ide et al 2005 ; Julius 2008 ; Hashioka et al 2009 ; Tong et al 2010 ; Tian et al 2013 ; Woodling et al 2014 ; Majer 2015 ; Freeman and Ting 2016 ; Vélez et al 2016 ; Watson et al 2016 ; Mez et al 2017 ; Su et al 2018 ; Choubey 2019 ; Dabin 2019 ; Hirsch et al 2019 ; Liu et al 2019 ; Majer et al 2019 ; Meyer et al 2019 ; Thatra 2019 ; Bellenguez et al 2020 ; Dabin et al 2020 ; Donaldson et al 2020 ; Martinelli et al 2020 ; Wang et al 2020 ; Vastrad and Vastrad 2021 ). Notably, the EMMAX GxE mixed model solutions were also robust to the inclusion of additional fixed effect covariates (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Hirsch et al. discovered that inhibition of histone deacetylase might alleviate abnormalities in the Notch and Eph axis in prion protein PrP deficient and prion-infected cells ( 87 ). Besides, studies have demonstrated that lncRNA HOTAIR induces OC drug resistance to cisplatin through activating the Wnt/β-catenin pathway ( 88 ).…”
Section: Epigenetic Modifications In Oc Drug Resistancementioning
confidence: 99%
“…Prions play a crucial role in neurodegenerative diseases, where normal PrPc is converted into a misfolded scrapie isoform called PrPSc pathogenic, which provides a seeding mechanism for the propagation of pathogenic prions [146]. In neuronal cells, the above conversion leads to molecular and functional alterations that impact synaptic plasticity.…”
Section: Prions and Epigenetic Inheritancementioning
confidence: 99%
“…In neuronal cells, the above conversion leads to molecular and functional alterations that impact synaptic plasticity. Cells with PrPc depletion and prion infection show defects in two important signaling pathways, namely Notch and Eph, which are crucial for development and axon migration, respectively [146]. The defects are ameliorated by inhibiting histone deacetylase, hence, Notch and Eph pathways are epigenetically regulated by prion [146].…”
Section: Prions and Epigenetic Inheritancementioning
confidence: 99%